Couples and parenting dynamics during Covid-19 pandemic: A systematic review of the literature - Maria Leonor Sentieiro; Luana Cunha Ferreira; Mariana Pires de Miranda; Beatriz Araújo Vitória (PLoS ONE, 2025)
The COVID-19 pandemic constituted a public health crisis bound to impact couples, parents, and families globally. However, the literature on the impacts of COVID-19 in families is not yet integrated. This systematic review aims to (1) provide an overview of how the COVID-19 pandemic potentially changed family systems, especially the couples and parenting dynamics, as well as (2) integrate inconsistent findings, and, finally, (3) define new avenues for research and clinical practice. Inclusion and exclusion criteria were defined for this review. The data was collected in bibliographic databases using a combination of keywords. The study includes empirical research published in English, Spanish, Italian, or Portuguese, appearing in peer-reviewed journals, focusing on the impact of the COVID-19 pandemic on the functioning of different-gender or same-gender couples, married or cohabitating, or cohabitating parents with children aged 2 to 18, between April 2020 and December 2023. Within 381 articles, 58 studies met the inclusion criteria, which 50 were quantitative, four qualitative, and four mixed methods studies. A qualitative thematic analysis of the reviewed articles identified 12 categories that were organized by stress sources, mediators, and outcomes. There is consistent evidence across the literature showing some sources of stress during COVID-19, such as Gender Inequalities (e.g., Unequal Division of Household Duties and Lack of Support for Mothers), and External Stress. Also, we identified some themes on the mediators such as Coping Strategies (e.g., Dyadic Support, Communication as a Mediator and Adaptation to New Daily Routines) and finally as outcomes, Lower Psychological Well-Being, and Relational Growth. However, some inconsistencies were found in Relationship (In) Satisfaction, Sexual Functioning and Communication as an Outcome. Explorations of moderators showed that these inconsistencies should be understood in reference to (1) quality assessment (2) coping and (3) income. After conducting a comprehensive analysis of inconsistencies, our study revealed no notable differences in either relationship satisfaction or sexual frequency before and after the COVID-19 pandemic. Notably, a decline in sexual satisfaction was observed during the COVID-19 period. No conclusive associations were identified between income, relationship satisfaction, sexual satisfaction, sexual frequency, and stress related to COVID-19. Nonetheless, our observations indicated that individuals with moderate or high income, in conjunction with the implementation of effective coping strategies, exhibited a diminished impact of COVID-19-related stress on both relationship satisfaction and sexual functioning. Future studies should focus on a dyadic perspective at various stages of the family cycle, including longitudinal perspectives, as well as studies focused on the role of dyadic coping during times of crises. Findings must be considered with caution because not all studies had equal methodological rigor.